THE INFLUENCE OF DISLOCATIONS ON THE LATENT TECHNOLOGICAL ENERGY OF MACHINE PARTS - З. А.Шодмонкулов (Modern American Journals, 2025)
A dislocation model for the formation of technological residual stresses is presented, and its intensity is evaluated through an energy criterion of the surface layer quality of machine parts – the latent (stored) deformation energy. Abrasive blasting of the side surfaces of the teeth of saw blades of a cotton processing machine with black silicon carbide particles is proposed. The required processing quality is achieved by forming an effective microrelief on the treated surface.
Keywords: Residual micro- and macrostresses, dislocation, dislocation density, plastic deformation, structural elements, structural-energy model, latent energy, strain hardening, stress intensity, saw blade, abrasive blasting.